Managerial economics : problem-solving in a digital world - Wilkinson, Nick (Cambridge University Press, 2022)
Managerial economics, meaning the application of economic methods in the managerial decision-making process, is a fundamental part of any business or management course. The current business environment presents managers with increasingly difficult decisions, amidst the Covid-19 pandemic and associated lockdowns, as well as the digital revolution and improved technology. Now in its second edition, this textbook features a new focus on how managerial economics has been transformed by the increasing importance of digitization within both the workplace and wider economy. It also features a new chapter on consumer theory, which emphasizes psychological factors and behavioural economics. Wilkinson adapts a user-friendly problem-solving approach to take the reader in gradual steps from simple problems through increasingly difficult material to complex case studies, demonstrating how to apply the principles of managerial economics to real-life situations.